Physical Activity's Impact on Anxiety Management : A Systematic Review - Richard Peter, Bailey; Nadia, Samsudin; Francis, Ries; Motevalli, Saeid; Mansor, Abu Talib; Janet Ann, Fernandez; Tan, Li Huan (International Society for Comparative Physical Education and Sport, 2025)
Anxiety is a prevalent mental health concern among adolescents, which has prompted an increase in research examining the potential benefits of physical activity (PA) interventions. While PA has been explored as a potentially efficacious approach, research findings remain fragmented. The findings from 12 studies, analysed using the PRISMA framework, highlight the significant role of PA in managing anxiety among adolescents. Notably, higher levels of PA were linked to lower anxiety levels and a lower prevalence of anxiety-related symptoms. Despite the fact that some studies revealed gender and age-dependent differences in anxiety outcomes, a consistent trend highlighted the overall beneficial effects of PA. Thus, these studies demonstrate that PA interventions may effectively reduce anxiety in adolescents. Encouragement of PA, particularly in school and community contexts, emerges as an effective and accessible strategy for promoting the mental health of adolescents. These results support incorporating PA initiatives into larger mental health promotion and management programmes for this vulnerable population, offering valuable insights for policymakers and educators.